Malaria and anemia in children under 7 years of age in the western region of Côte d’Ivoire - Ehouman, Mocket Adolphe; N’Goran, Kouakou Eliezer; Coulibaly, Gaoussou (Frontiers in Tropical Diseases, 2022)
Background: Anemia is a major public health problem affecting nearly a quarter of the world's population. It’s defined as a reduction in the hemoglobin level in the peripheral blood below the normal threshold set for a particular population. Very commonly in the subtropics, helminthes or malaria co-infects the same person, causing morbidities that vary according to age and region. This research study aims to characterize the type of anemia observed in anemic children in the Western part of Côte d`Ivoire, in order to recommend better strategy of care. Methods: The study was carried out from March 2020 to May 2021 in 22 villages of the “Tonkpi Region” (Man). A total of 451 children of both sex, aged 3 months to 6 years provided venous blood samples that were subjected to a FBC (diagnosis of anemia and it characterizations) as well as the RDT and Giemsa stain- thick and thin smear (GS) for the diagnosis of malaria. Risk factors and morbidity profiles were assessed using a questionnaire. Logistic regressions models were employed to identify independent risk factors and morbidity patterns associated with P. falciparum mono- and co-infections. Results: Among 451 selected children who completed the study, 221(49.0%) were females and 230(51.0 %) were males. The prevalence of anemia was 55.0%, distributed as 30.7% mild, 66.1% moderate and 3.2% severe anemia. The characterization of the anemia revealed that hypochromic microcytic anemia (HMA) was predominant with 195(78.63%) children. It was followed by normochromic microcytic anemia 29(11.69%), normochromic normocytic anemia 14(5.65%) and lastly, hypochromic normocytic anemia 10(4.03%). The prevalence of malaria was 66.7% and 78.3% on the basis of the GS and RDT respectively. Conclusion: Malaria infection was highly prevalent among children aged ≤7 years in both gender and age groups, although the malaria parasites tend to infect lesser younger children compare to older ones. The prevalence of anemia is high with moderate anemia and HMA being more prevalent in children ≤7 years in the Western region. Indeed, 56.7% of mild, 51.3% of moderate and 37.5% of severe anemic children were infected with P. falciparum alone confirming the intertwine relationship between malaria and anemia.